College View Historic District : A case Study of Historic Preservation in Greenville, North Carolina - Benedict, Deann Lyn (East Carolina University, 2012)
During the period of urban renewal, especially during the 1970s and 1980s, Greenville, N.C. was losing much of its historic built environment. Concerned citizens joined together to establish the Historic Properties Commission in 1979. This began the preservation movement in Greenville, N.C.   The city, by request of the Historic Properties Commission, hired Kate Ohno to complete a survey of the built environment and write a report based on the findings. In her report she made recommendations as to which neighborhoods and individual properties should be nominated to the National Register of Historic Places and which should be considered for local historic district designation or landmark status.   The Historic Properties Commission evolved into the Greenville Area Preservation Association. Mrs. Ohno's report continued to guide the preservation efforts in Greenville. Individual properties remained the focus until the end of the 1980s when the College View neighborhood became the focal point. During this same period the Historic Preservation Commission was established by the City Council.  The Historic Preservation Commission followed the recommendations outlined in Mrs. Ohno's report that had by this point been published by the Greenville Area Preservation Association in The Architectural Heritage of Greenville, North Carolina. College View was the first neighborhood chosen to be nominated to the National Register of Historic Places; it was listed on March 19, 1992. College View was chosen because of the density of original structures, the deterioration of the neighborhood caused by the high student renter population, and the encroachment of the university.  Issues arose among the city, the preservationists, and the university due to each party having its own agendas, uses, and future intentions for the neighborhoods. In the end College View became both the first National Register District and in 2012 the only local historic district in Greenville, N.C. The real legacy of the preservationists is not what they accomplished in College View but what followed it.  In 2012 not all of the goals for the College View Historic District have come to fruition. The biggest disappointment has been the renter/owner ratio. The preservation efforts have continued to impact Greenville. Four more neighborhoods were nominated to the National Register; these include the Greenville Tobacco Warehouse District, the Greenville Commercial Historic District, the Skinnerville/Greenville Heights Historic District, and the Dickinson Avenue Historic District. Due to public support, historic preservation has become a part of the city's plan for its future within the Horizons Plan, although it is not a fully integrated planning component.
Keywords: History; American history; Area planning and development; Greenville (N.C.); Historic districts; Historic preservation; National register; Greenville (N.C.)--History; Historic preservation--North Carolina--Greenville; Historic districts--North Carolina--Greenville; East Carolina University--Student housing; Community and college--North Carolina--Greenville; College View Historic District (Greenville, N.C.)